2021
DOI: 10.3390/s21041180
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Mobile Laser Scanning towards Operational Accurate Road Rut Depth Measurements

Abstract: This paper studied the applicability of the Roamer-R4DW mobile laser scanning (MLS) system for road rut depth measurement. The MLS system was developed by the Finnish Geospatial Research Institute (FGI), and consists of two mobile laser scanners and a Global Navigation Satellite System (GNSS)-inertial measurement unit (IMU) positioning system. In the study, a fully automatic algorithm was developed to calculate and analyze the rut depths, and verified in 64 reference pavement plots (1.0 m × 3.5 m). We showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Fryskowska et al [16] found that the relative accuracy achievable with an MLS survey is on the order of a few millimeters, even in the elevation component up to distances of approximately 5 m from the laser sensor, i.e., in a distance range in line with that used in the survey of the road surface. Same-order accuracy results are achieved by El Issaoui et al [15], who analyze the accuracy of MLS-derived rut depths by comparing them with rut depth derived from a static Terrestrial Laser Scanners (TLS) survey. The authors also compare the cross slopes obtained with both techniques.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Fryskowska et al [16] found that the relative accuracy achievable with an MLS survey is on the order of a few millimeters, even in the elevation component up to distances of approximately 5 m from the laser sensor, i.e., in a distance range in line with that used in the survey of the road surface. Same-order accuracy results are achieved by El Issaoui et al [15], who analyze the accuracy of MLS-derived rut depths by comparing them with rut depth derived from a static Terrestrial Laser Scanners (TLS) survey. The authors also compare the cross slopes obtained with both techniques.…”
Section: Introductionmentioning
confidence: 73%
“…This configuration, at 6 m distance, is compatible with a grid size of 8 mm (Figure 13). In correspondence to the curve section, in the concave inner part at 6 m from the roadway axis, we computed the decrease in the grid spacing with Equation (15). This was used to produce the graph in Figure 6, given the curve radius (about 45 m), which was equal to about 0.7 mm; hence, the grid spacing along the concave edge, in the longitudinal direction, assumed a value equal to 8.3 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potholes, which are typically over 10 cm in diameter and multiple cm deep, can be robustly identified with centimeter-level accuracy. El Issaoui et al [33] deem a 1.4 mm error level adequate for operational rut depth measurements. For reference use, sub-millimeter levels of accuracy and precision are necessary to reliably evaluate various defect types.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, comparisons allow us to determine deviations between modeling methods and to establish any systematic failures in instruments. Additionally, the use of established and wellcalibrated methods, such as terrestrial laser scanning (TLS), which can be considered accurate within its calibrated accuracy, provides a reliable baseline [33]. However, TLS data may be too sparse for accurate quantification of pavement defects.…”
Section: Distress Type Mechanism Manifestationmentioning
confidence: 99%